2022
DOI: 10.1371/journal.pone.0268160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating diagnostic accuracies of Panbio™ test and RT-PCR for the detection of SARS-CoV-2 in Addis Ababa, Ethiopia using Bayesian Latent-Class Models (BLCM)

Abstract: Background Rapid diagnostics are vital for curving the transmission and control of the COVID-19 pandemic. Although many commercially available antigen-based rapid diagnostic tests (Ag-RDTs) for the detection of SARS-CoV-2 are recommended by the WHO, their diagnostic performance has not yet been assessed in Ethiopia. So far, the vast majority of studies assessing diagnostic accuracies of rapid antigen tests considered RT-PCR as a reference standard, which inevitably leads to bias when RT-PCR is not 100% sensiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
0
5
1
Order By: Relevance
“…Others studies of symptomatic patients in the Netherlands and Spain found similar test sensitivity (respectively, 72% and 71%) and specificity (respectively, 100% and 99%) 11,12 . In contrast, a study made in Ethiopia shows better sensitivity 99.6% and a specificity of 99.1% using Bayesian latent‐class models 13 . This difference could be explained by the size of our sample and the fact that we only specify symptomatic patients.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…Others studies of symptomatic patients in the Netherlands and Spain found similar test sensitivity (respectively, 72% and 71%) and specificity (respectively, 100% and 99%) 11,12 . In contrast, a study made in Ethiopia shows better sensitivity 99.6% and a specificity of 99.1% using Bayesian latent‐class models 13 . This difference could be explained by the size of our sample and the fact that we only specify symptomatic patients.…”
Section: Discussionmentioning
confidence: 65%
“…11,12 In contrast, a study made in Ethiopia shows better sensitivity 99.6% and a specificity of 99.1% using Bayesian latent-class models. 13 This difference could be explained by the size of our sample and the fact that we only specify symptomatic patients.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations